Implementation of Corporate Social Responsibility (CSR) by PT. Equity World Futures (EWF) to Stakeholders (Employees) in Semarang City - Fatih Rafi Andanata; Siti Malikhatun Badriyah (International Journal Labs, 2025)
This research aims to examine the implementation of Corporate Social Responsibility (CSR) at PT. Equity World Futures (EWF) for its stakeholders, specifically employees in Semarang City. The study uses a descriptive analytical method to evaluate CSR regulations in Indonesia and assess how CSR is implemented at PT. EWF. The research findings reveal that CSR activities at PT. EWF include the provision of incentives, assistance, and facilities tailored to the needs of employees, such as health insurance, bonuses, and training programs. The company's CSR initiatives have contributed to a positive image and improved employee productivity. Furthermore, the CSR programs have been well-received by employees, with many reporting increased job satisfaction and a better work environment. However, some employees expressed the need for improvements in the implementation of CSR initiatives to meet their expectations fully. In conclusion, the CSR programs at PT. EWF Semarang have been beneficial in fostering good relationships between the company and its employees, improving productivity, and enhancing the company's overall reputation. The study suggests that continuous CSR improvements will strengthen employee engagement and support the company’s long-term success.